After that night [compact disc, unabridged] - Slaughter, Karin, 1971- (Slaughter, Karin, 1971- Will Trent series., 2023)
Fifteen years ago, Sara Linton's life changed forever when a celebratory night out ended in a violent attack that tore her world apart. Since then, Sara has remade her life, until one evening, on call in the ER, everything changes. Sara battles to save a broken young woman who has been brutally attacked. But as the investigation progresses, led by GBI Special Agent Will Trent, it becomes clear that Dani Cooper's assault is uncannily linked to Sara's.